Development of Microteaching Guide Book Based on Hybrid Learning to Improve Teaching Skills of Prospective Teachers - Dame Taruli; Risden Anakampun; Taripar Samosir; Andrianus Nababan; Maria Widiastuti (AL-ISHLAH: Jurnal Pendidikan, 2023)
The lack of microteaching guidebooks makes prospective teacher students confused when preparing microteaching lessons. This development research aimed to produce a Micro Teaching Teaching Material Book Based on Hybrid Learning to improve the Teaching Ability of Christian Religious Education Prospective Teachers at Tarutung IAKN Christian Religious Education Study Program. The type of research and development research method used was a quantitative method. This study adapts and combines the CDP (Courseware Development Process) instructional development model, with development research procedures, according to Borg and Gall. The six stages of developing the CDP instructional model include: l) analysis, 2) design, 3) development, 4) formative evaluation, 5) implementation, and 6) summative evaluation. Operational testing of the product was a manual, electronic manual and electronic micro teaching-based teaching book for hybrid learning. The results of the validation in the form of expert assessments of material, media, and language expert lecturers and products in the feasibility test of micro-teaching guidebooks based on hybrid learning to students in field trials were 90.78%. So it can be concluded that the feasibility of micro-teaching guidebooks based on hybrid learning for students and lecturers in field trials is included in the very feasible and valid category to be used as teaching materials.